Biosynthesis of ZnO Nano-particle and its quality evaluation on the shelf life extension of fruit - Yasmin, Farzana; Hossain, Md. Murad; Nurul, Huda; Maryani, Anis Tatik; Zzaman, Wahidu (Indonesian Food Science and Technology Journal, 2023)
Consumers around the world want fruits with high quality, without chemical preservatives, and with an extended shelf life. Edible films and coating received a considerable amount of attention in recent years because they are useful and beneficial over synthetic packaging. Prolonging of shelf life of food is an important goal to be attained. Many storage techniques have been adapted to extend the marketing distance and holding periods for commodities after harvest. Edible coatings are thin layers of edible material applied to the product surface to provide a barrier to moisture, oxygen, and solute movement for food. The purpose of this study was to produce bio-synthesized ZnO Nano-particles from spinach. The coating solution is prepared by mixing Nano-particles with chitosan-acetic acid solution and evaluates the shelf-life after treatment as a coating. The study showed that coated fruit maintained its quality up to 28 days of the study period. Thus, it can be concluded that ZnO Nano-particles can be used as a coating for increasing shelf-life.